Digital Marketing Tools’ Transformative Role in Sustainable Development: Navigating Limited Mobility and Disrupted Infrastructure Worldwide - Tanasiichuk, Alona; Lozovska, Ganna; Znachek, Rafaela; Shevchuk, Anna; Voitovych, Sergii; Pavlenko, Olena; Danyliuk, Oleksandr (European Journal of Sustainable Development, 2025)
This study explores the transformative role of digital marketing in promoting sustainable development amid global crises-specifically war, restricted mobility, and disrupted infrastructure. Using Ukrainian organic cosmetics (HS 3304) as a case, it evaluates export opportunities to high-potential markets such as the UK, France, the Netherlands, Belgium, Canada, Singapore, Australia, and Japan. These markets feature strong demand for natural, ethical, and innovative products. Digital marketing is framed as a strategic instrument, supporting not only international promotion but also economic resilience, sustainability, and social recovery. It allows businesses to communicate without physical presence—vital during wartime-and optimize logistics, update consumers in real time, and ensure operational continuity despite infrastructure damage. Consumer-behavior analysis using SEMrush, Ahrefs, Google Trends, and social media listening shows consistent growth in organic, vegan, and sustainable beauty themes, while niche segments remain underserved with low competition and marketing costs-ideal for Ukrainian producers. The research highlights digital marketing’s role in supply chain flexibility, enabling rerouting, risk mitigation, and demand forecasting. It also supports the creation of digital products-virtual showrooms, AR tools, e-commerce, and chatbots—ensuring ongoing engagement during mobility restrictions. Environmental and social benefits are also emphasized: companies can reduce emissions, cut print and event-related transport, and involve consumers in crowdfunding and sustainability efforts. Finally, tools like Trade Map and The Global Economy help assess export potential, identify market trends, and guide entry strategies. The study offers a roadmap for Ukrainian businesses, positioning digital marketing as a critical lever for survival, growth, and integration into the global sustainable economy. Keywords: digital marketing, sustainable development, social resilience, economic resilience, environmental balance, consumer environmental behaviour, social inclusion, organic cosmetics, export, restricted mobility, logistics, logistical processes, supply chains, omnichannel marketing, crisis marketing, e-commerce, market analytics, business intelligence, ESG, ESG reporting, business processes, digital products and services, social media, email marketing, mobile applications, chatbots, online services, platform solutions, low-code/no-code platforms, crowdfunding, green content marketing, zero-waste, cruelty-free, consumer-behaviour trends, SEMrush, Ahrefs, logistics management, marketing research.